Index to Philippine periodicals, 1995-2000 (University Library, UP Diliman, 2001)
The IPP 1995-2000 is a cumulative index to popular and scholarly periodicals published in the Philippines from 1995 to 2000. It consists of bibliographic descriptions of the articles and is searchable by subject and author.